Internal Audit Guidelines For Risk-Based Maqāṣid Syariah - Siti Umi Nurbaidah; Ahmad Fauzi (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
This article develops a new conceptual framework for the Risk-Based Internal Audit of Sharia Maqāṣid (IARBMS) by integrating the principles of risk-based internal audit (RBIA) and the normative objectives of maqāṣid sharia as the foundation of sustainability-oriented governance. This study uses a qualitative approach based on conceptual, comparative analysis, and literature synthesis to formulate maqāṣid risk indicators, risk assessment tables, and risk registers that are applicable to Islamic financial institutions. The results of the analysis show that the implementation of IARBMS not only improves the effectiveness of risk management and sharia compliance, but also strengthens governance, information integrity, asset security, and the socio-environmental contribution of institutions. This framework offers theoretical contributions through the elaboration of institutional maqāṣid as well as practical contributions in the form of audit guidelines that can be adopted by internal auditors, regulators, and sharia supervisory boards. The implications of the research confirm the need for standardization of maqāṣid audits in the global Islamic finance industry.